2019
DOI: 10.1007/s00167-019-05541-z
|View full text |Cite
|
Sign up to set email alerts
|

The Chinese ACL injury population has a higher proportion of small ACL tibial insertion sizes than Western patients

Abstract: Purpose The study purpose is to characterize the sizes of the anterior cruciate ligament (ACL) insertion site and intercondylar notch in Chinese patients undergoing ACL surgery. The findings will provide a reference for individualized clinical treatment of ACL rupture. Methods For this study, 137 patients (102 males, 35 females) with an average age of 30.3 ± 9.5 years (range 14-52 years) undergoing ACL reconstruction were included. The tibial ACL insertion site length and width and the intercondylar notch widt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Injury trends within the Women’s National Basketball Association (WNBA) help illustrate potential disparities by race, with White athletes having more than 6 times the ACL tear rate of other ethnic groups combined [ 83 ]. Data of Han Chinese patients with ACL injuries shows a higher proportion of patients with a small tibial footprint size compared to Western populations with ACL injuries, suggesting differences in tibial footprint size could play a role between races [ 84 , 85 ]. There is a paucity of studies and limited data on racial and ethnic predisposition to ACL injury despite well-described anatomic differences.…”
Section: Disparities In Race and Ethnicitymentioning
confidence: 99%
“…Injury trends within the Women’s National Basketball Association (WNBA) help illustrate potential disparities by race, with White athletes having more than 6 times the ACL tear rate of other ethnic groups combined [ 83 ]. Data of Han Chinese patients with ACL injuries shows a higher proportion of patients with a small tibial footprint size compared to Western populations with ACL injuries, suggesting differences in tibial footprint size could play a role between races [ 84 , 85 ]. There is a paucity of studies and limited data on racial and ethnic predisposition to ACL injury despite well-described anatomic differences.…”
Section: Disparities In Race and Ethnicitymentioning
confidence: 99%
“…For these reasons, the ACL has been the subject of many anatomical studies, and recent studies have used advances in technology to better control knee loading during measurement and more accurately characterize the complex tissue morphology. Most studies have described the native ACL as having an hourglass shape with direct midsubstance attachments and thin, membranous, peripheral attachments, at both the femoral and tibial insertion sites [1, 3, 5, 6, 8, 10]. Harner et al, used a digital measurement system to quantify the ACL dimensions and found that the cross‐sectional areas at the femoral and tibial insertion areas were over three times larger that of the midsubstance cross‐sectional area [6].…”
Section: Introductionmentioning
confidence: 99%
“…Our ndings suggest that the prevalence of noncontact ACL injuries and associated posterolateral tibial plateau fractures in our East China cohort is lower than previously documented in European and American populations. Differing femoral and tibial morphologies attributable to racial variations may account for this discrepancy (19)(20)(21)(22)(23). Other factors include China's national conditions, such as the widespread use of motorized two-wheelers and the lower engagement in contact sports, although the true incidence of ACL injuries in the vast Chinese population remains largely unquanti ed.…”
Section: Discussionmentioning
confidence: 99%